2014
DOI: 10.1163/15691624-12341269
|View full text |Cite
|
Sign up to set email alerts
|

Desire for Higher Education in First-Generation Hispanic College Students Enrolled in a Graduate Counseling Program

Abstract: Motivation to seek higher education is rarely examined in Hispanic first-generation graduate students, those v^ihose parents have not attended college, and there is less literature examining those whose desire for education extends to a master's degree in counseling. The purpose of this study was to conduct a phenomenological examination of the desire to attend college among first-generation Hispanic students enrolled in a counselor education program. One-hour taped interviews were conducted with three volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Martina, Lucia, and Marisol also seemed to perceive a harsh division between their ethnic identities and academia. In support of this finding, Olive () found that cultural factors interacted with the studies of Hispanic counseling graduate students. Olive's findings also highlighted the impact that a lack of familial role models seeking higher education had on the students’ decisions to seek graduate degrees and how their spiritual beliefs interfaced with their career choice in that the students viewed counseling as a way to fulfill an “altruistic motivation” (p. 80).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Martina, Lucia, and Marisol also seemed to perceive a harsh division between their ethnic identities and academia. In support of this finding, Olive () found that cultural factors interacted with the studies of Hispanic counseling graduate students. Olive's findings also highlighted the impact that a lack of familial role models seeking higher education had on the students’ decisions to seek graduate degrees and how their spiritual beliefs interfaced with their career choice in that the students viewed counseling as a way to fulfill an “altruistic motivation” (p. 80).…”
Section: Discussionmentioning
confidence: 88%
“…Yet only two of the 19 participants were Hispanic. Olive () conducted a phenomenological study focused on Hispanic master's‐level counseling students. Unique factors not described elsewhere included a lack of family role models who attended college, spiritual values that influenced the decision to pursue graduate education in counseling, and a desire to use one's counseling degree altruistically.…”
Section: Relevant Research In Higher Educationmentioning
confidence: 99%
“…The "Campus Life" discourse promotes an experience outside of academia, one that is social and recreational with numerous opportunities for the student. Olive (2009) stressed that a comfortable academic environment influences first-generation Hispanic college students' desire for higher education, and Cortes (2011) found that campus climates that validate Hispanic culture and promote collaboration also attract Hispanics to institutions. The HSIs and non-HSIs both demonstrate discursive properties that might be appealing to Hispanic students and validate Hispanic culture, such as religious information, value systems that align with Hispanic cultural values, subtle ethnic cues, and programming and student clubs that cater to diverse students.…”
Section: Race/culture/diversitymentioning
confidence: 99%
“…• Entertainment and Engagement Some papers focused on the desire and motivation to pursue higher education. Olive (2009) found that for Hispanic students in the McNair program, their motivation came from a desire for self-improvement and giving back to their communities. The use of targeted McNair style programs involving video tutorials found that first generation students had a range of motivations and circumstances, from a desire to adapt to graduate school culture to a drive to defy expectations.…”
Section: • Validation and Supportmentioning
confidence: 99%
“…students must be part of undergraduate and graduate tutorial and mentoring indicatives (Olive, 2009).…”
Section: Schoolmentioning
confidence: 99%